Experimental and theoretical determination of the role of ions in atomic layer annealing. Issue 14 (17th March 2022) - Ueda, Scott T.; McLeod, Aaron; Jo, Youhwan; Zhang, Zichen; Spiegelman, Jacob; Spiegelman, Jeff; Alvarez, Dan; Moser, Daniel; Kanjolia, Ravindra; Moinpour, Mansour; Woodruff, Jacob; Cho, Kyeongjae; et al.
Abstract : The use of a heavier noble gas such as Kr in atomic layer annealing results in higher crystallinity due to higher momentum transfer leading to a more localized and intense surface heating effect occurring over picosecond timescales. Abstract : The atomic layer annealing process has recently shown promise as a technique for the deposition of crystalline materials that can be performed at the low temperatures of atomic layer deposition. However, the precise mechanism of the crystallization effect has not yet been thoroughly explored. In the present study, independent experimental control of ion momentum and energy are used in conjunction with molecular dynamics simulations to elucidate the role of ion energy and mass in atomic layer annealing. It was found that via a momentum transfer process, ions can displace surface atoms during initial contact and that they later induce a short-lived local heating phenomenon in the first few atomic layers, resulting in enhanced crystallinity. It was seen that by using a heavier gas such as Kr, energy transfer to the growth surface could be improved for AlN deposition, enabling the repair of a wider variety of crystallographic defects.